Protect crops naturally - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Natural Crop Protection in the Tropics. Letting Information Come to Life By G Stoll. Margraf Verlag, co-publication Agrecol and CTA, 2000. 386 pp. ISBN 3 8236 1317 0 Margraf Verlag PO Box 1205, 97985 Weikersheim, Germany. Fax: +49 7934 8156; Email:m